A woman school teacher an exploration of her concepts of the feminine roles, professional membership role and professional self-image - Ramos, Maria Dolores V. 1931- (s.n.], 1969)
The aim of the study is to describe the concepts of the feminine role, professional membership role and professional self-image of female school teachers in Bacolod City, who are in general, single, holder of a Bachelor's Degree and belonging to the lower-middle socio-economic class. The instruments used for this investigation are the following: (1) the Feminine Role Rating Inventory to identify the concept of the feminine role of teachers (2) 102 questions patterned after Dr. Richard L. Simpson's tool to measure the degree of the teachers' professional self-image and (3) the Sentence Completion Test to measure the size and extent of their professional membership.